Tunable and omnidirectional filters based on one-dimensional photonic crystals composed of single-negative materials - Mishra A.; Kumar Awasthi S.; Kumar Srivastava S.; Malaviya U.; Ojha S.P. (My University, 2025)
Tunable and omnidirectional filters have been demonstrated theoretically, using one-dimensional photonic crystals composed of single-negative materials. It is seen that a bilayer eight period structure can act as a tunable filter, which is sensitive to incident angle but insensitive to polarization. By increasing the number of periods to 16 and by tailoring the layer thicknesses, the same structure can act as an omnidirectional, polarization-independent filter for angles of incidence between 0° and 75°. © 2011 Optical Society of America.